SISTEM PENDUKUNG KEPUTUSAN KELOMPOK PENENTUAN KELAYAKAN LOKASI PEMUKIMAN DENGAN MENGGUNAKAN METODE ENTROPY, VIKOR, DAN COPELAND SCORE (Studi Kasus : Pemerintah Kota Lhokseumawe) - , mutammimul ula, Dr. Azhari SN., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
As vurnerable area of tsunami disaster, and sea wave abration, need a proper location to be a residence to support economic development, facility and infrastructure, and economic social in Lhokseumawe City Government. Therefore, decision of proper residence location needed to recommended as a residence will build. Evaluation to physical residence area, facility and infrastructure, and social economic also needed, which will be recommended as a residence location. Society input deeply needed to figure the location problems which will be recommended as a residence area. These will be done so the administrative found out and anticipate the problem occurs at the location. Application of Group Decision Support System (GDSS) which build using VIKOR (Vlse Kriterijumska Optimizacija Kompromisno Resenje in Serbia) method helped the decision maker to rank each alternative solution value, entropy as quality of each criterion. Meanwhile Copeland Score Method, as one of the voting method technically based on reducing victorious frequency with the lost frequency of the paired comparison to vote against solution the decision maker will be taken.